Arts of Life: A Place for Artists to Participate and Engage - Lydia Royeen (Scholarworks @ WMU, 2016)
Arts of Life is an innovative, Chicago-based day program where artists with and without disabilities have the opportunity to participate in artwork. It was created out of an identified need for individuals with a developmental disability to foster community engagement in artistic endeavors. Arts of Life has its foundation in four core values: inspiring artistic expression, building community, promoting self-respect, and developing independence. It bases its programming on these values, which help to maintain a collective environment that promotes artistic freedom for all individuals.